2017
DOI: 10.3390/ijerph14050532
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nano-Hydroxyapatite on the Metal Bioavailability, Plant Metal Accumulation and Root Exudates of Ryegrass for Phytoremediation in Lead-Polluted Soil

Abstract: Lead is recognized as one of the most widespread toxic metal contaminants and pervasive environmental health concerns in the environment. In this paper, the effects of nano-hydroxyapatite (NHAP) on remediation in artificially Pb-contaminated soils and ryegrass were studied in a pot experiment. The addition of NHAP decreased the water- and acid-soluble, exchangeable, and reducible fractions of Pb, extracted using the Community Bureau of Reference (BCR) method, whilst greatly increasing the residual fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…The results from the aforementioned research provided beneficial information about the influence of nano-hydroxyapatite on the removal of lead, which plays a significant role in phytoremediation. The authors of [100] illustrated that nano-hydroxyapatite can effectively decrease the mobility and bioavailability of lead. The incorporation of nano-hydroxyapatite significantly decreased the reducible and exchangeable segments of lead in soil and converted these segments into an oxidizable and residual lead, thereby restricting its mobility as well as its bio-accumulating ability.…”
Section: Nano-hydroxyapatite (Nhap) As Nano-fertilizersmentioning
confidence: 99%
“…The results from the aforementioned research provided beneficial information about the influence of nano-hydroxyapatite on the removal of lead, which plays a significant role in phytoremediation. The authors of [100] illustrated that nano-hydroxyapatite can effectively decrease the mobility and bioavailability of lead. The incorporation of nano-hydroxyapatite significantly decreased the reducible and exchangeable segments of lead in soil and converted these segments into an oxidizable and residual lead, thereby restricting its mobility as well as its bio-accumulating ability.…”
Section: Nano-hydroxyapatite (Nhap) As Nano-fertilizersmentioning
confidence: 99%
“…HAP has a unique hydroxyl group that enhances soil pH, diminishing the solubility of heavy metals, such as Cd and Pb, by forming chelate or precipitate substances to change heavy metal bioavailability and reduce phytotoxicity [ 17 , 18 , 19 , 20 ]. HAP can not only directly immobilize heavy metals, leading to reduced heavy metal toxicity, but also improve plant growth and biomass, and reduce heavy metal content in plant tissues [ 21 , 22 ]. Meanwhile, HAP can be considered an inorganic P fertilizer, providing P nutrition for plants.…”
Section: Introductionmentioning
confidence: 99%
“…Application of NMs improved yield growth and components of peanut as stated in the presented data (Table 5). This finding may be mainly due to the improved physical and chemical properties of soil and availability of different nutrients, particularly phosphorus (Amira et al, 2016;Ling et al, 2017;Xing et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to high adsorption capacity, high stability, and low water solubility (Doaa et al, 2016;Mobasherpour et al, 2011;Xenidis et al, 2010;Zhang et al, 2010). The application of HapNP decreased exchangeable and reducible fractions of Pb in the soil, and converted them into oxidizable, reducing their susceptibility to availability (Ling et al, 2017;Seleiman & Kheir, 2018). Zhang et al (2019) found that micro-hydroxyapatite and nanohydroxyapatite were used to reduce available HM, increase the diversity of the fungal community and increase soil pH in contaminated soil.…”
mentioning
confidence: 99%